Comparative transcriptomic analysis of PK15 cells infected with a PRV variant and the Bartha-K/61 vaccine strain - Zhang, Hongliang; Duan, Xiaoxiao; Liu, Gang; Li, Yingguang; Dong, Shaoming; Lin, Jiaxu; Zhang, Ruihua; Cai, Xiulei; Shan, Hu (Frontiers in Microbiology, 2023)
Pseudorabies virus (PRV) is a herpesvirus that can infect domestic animals, such as pigs, cattle and sheep, and cause fever, itching (except pigs), and encephalomyelitis. In particular, the emergence of PRV variants in 2011 have resulted in serious economic losses to the Chinese pig industry. However, the signaling pathways mediated by PRV variants and their related mechanisms are not fully understood. Here, we performed RNA-seq to compare the gene expression profiling between PRV virulent SD2017-infected PK15 cells and Bartha-K/61-infected PK15 cells. The results showed that 5,030 genes had significantly different expression levels, with 2,239 upregulated and 2,791 downregulated. GO enrichment analysis showed that SD2017 significantly up-regulated differentially expressed genes (DEGs) were mainly enriched in the binding of cell cycle, protein and chromatin, while down-regulated DEGs were mainly enriched in ribosomes. KEGG enrichment analysis revealed that the pathways most enriched for upregulated DEGs were pathways in cancer, cell cycle, microRNAs in cancer, mTOR signaling pathway and autophagy-animal. The most down-regulated pathways of DEGs enrichment were ribosome, oxidative phosphorylation, and thermogenesis. These KEGG pathways were involved in cell cycle, signal transduction, autophagy, and virus-host cell interactions. Our study provides a general overview of host cell responses to PRV virulent infection and lays a foundation for further study of the infection mechanism of PRV variant strain.